Dossier I: sobre perfiles geográficos de asesinos en serie - Úbeda Flores, Manuel (Quadernos de criminología, 2021)
The issue of serial killers is difficult to analyze. Attempts have been made to study their behaviors and modus operandi from various perspectives (psychological, sociological, biological, criminalistic, police and even mathematical). In this work we recall some relevant studies on geographic profiles that try to locate these murderers based on the data of their crimes and we provide a new study of these profiles using Thiessen polygons.